Управління ресурсним потенціалом інклюзивного розвитку підприємств в туризмі - Козоріз, Олександр Євгенійович; Kozoriz, Oleksandr (Запоріжжя : Видавничий дім «Гельветика», 2025)
UA: Дослідження присвячене обґрунтуванню теоретичних і прикладних засад управління ресурсним потенціалом інклюзивного розвитку підприємств в туризмі. Визначено структуру ресурсного потенціалу, що включає матеріальні, фінансові, людські, інформаційні, інтелектуальні та соціальні ресурси. Окреслено принципи їх узгодженого використання і наведено відповідні інструменти управління. Розроблено систему критеріїв і показників для оцінювання рівня ресурсного забезпечення інклюзивного розвитку. Створено практичну модель, що поєднує ресурсний, процесний і стейкголдерний підходи. Модель забезпечує перетворення ресурсів у соціально значущі результати та може застосовуватися підприємствами для підвищення конкурентоспроможності, зміцнення соціальної ефективності та впровадження інклюзивних бізнес-стратегій. /// EN: The article explores the theoretical and applied foundations of managing the resource potential of inclusive development in tourism enterprises. The study demonstrates that inclusive development requires more than basic accessibility measures. It depends on the coordinated use of material, financial, human, informational, intellectual, and social resources. These resources shape the enterprise’s capacity to support wider participation, improve service accessibility, and engage vulnerable groups in tourism activities. The research clarifies managerial principles that guide the effective use of resource potential. These principles emphasise system thinking, adaptability to change, involvement of stakeholders, digital transformation, and the creation of an inclusive organisational culture. The study identifies mechanisms that enable tourism enterprises to integrate inclusiveness into daily operations. These mechanisms include inclusive human-resource practices, evidence-based decision-making, structured knowledge management, partnership development, and specialised financialtools that support inclusive initiatives. A detailed system of criteria and indicators for assessing the level of resource provision is proposed. The system reflects both the availability and quality of resources and evaluates their contribution to social outcomes. Building on this assessment framework, the article introduces a practical model for managing resource potential. The model combines resource-based, process-oriented, and stakeholder perspectives. It demonstrates how resources are transformed into inclusive results through sequential managerial actions. This approach ensures continuity, accountability, and strategic alignment. The model is suitable for tourism operators, travel agencies, hotels, food services, and transport organisations. The study concludes that effective management of resource potential is essential for inclusive development in tourism. It strengthens the competitiveness of enterprises, enhances their social impact, and supports the broader community-oriented role of the tourism sector.
Management of resource potential for inclusive development of enterprises in tourism
Keywords: інклюзія; інклюзивний розвиток; ресурсний потенціал; управління ресурсами підприємства; інклюзивний розвиток в туризмі; inclusion; inclusive development; resource potential; enterprise resource management; inclusive development in tourism